Disparate effects of Shb gene deficiency on disease characteristics in murine models of myeloid, B-cell, and T-cell leukemia. Issue 4 (April 2018) - Jamalpour, Maria; Li, Xiujuan; Gustafsson, Karin; Tyner, Jeffrey W; Welsh, Michael
The Src homology-2 domain protein B is an adaptor protein operating downstream of tyrosine kinases. The Shb gene knockout has been found to accelerate p210 Breakpoint cluster region-cAbl oncogene 1 tyrosine kinase-induced leukemia. In human myeloid leukemia were tumors with high Src homology-2 domain protein B mRNA content, tumors were, however, associated with decreased latency and myeloid leukemia exhibiting immune cell characteristics. Thus, the aim of this study was to investigate the effects of Shb knockout on the development of leukemia in three additional models, that is, colony stimulating factor 3 receptor-T618I–induced neutrophilic leukemia, p190 Breakpoint cluster region-cAbl oncogene 1 tyrosine kinase-induced B-cell leukemia, and G12D-Kras-induced T-cell leukemia/thymic lymphoma. Wild-type or Shb knockout bone marrow cells expressing the oncogenes were transplanted to bone marrow–deficient recipients. Organs from moribund mice were collected and further analyzed. Shb knockout increased the development of CSF3R T618I -induced leukemia and increased the white blood cell count at the time of death. In the p190 Breakpoint cluster region-cAbl oncogene 1 tyrosine kinase B-cell model, Shb knockout reduced white blood cell counts without affecting latency, whereas in the G12D-Kras T-cell model, thymus size was increased without major effects on latency, suggesting that Shb knockout accelerates the development thymic lymphoma. Cytokine secretion plays a role in the progression of leukemia, and consequently Shb knockout bone marrows exhibited lower expression of granulocyte colony stimulating factor and interleukin 6 in the neutrophilic model and interleukin 7 and chemokine C-X-C motif ligand 12 (C-X-C motif chemokine 12) in the B-cell model. It is concluded that in experimental mouse models, the absence of the Shb gene exacerbates the disease in myeloid leukemia, whereas it alters the disease characteristics without affecting latency in B- and T-cell leukemia. The results suggest a role of Shb in modulating the disease characteristics depending on the oncogenic insult operating on hematopoietic cells. These findings help explain the outcome of human disease in relation to Src homology-2 domain protein B mRNA content.